The impact of delayed evacuation on the quality of human fetal tissue - Otaibi, Yasmeen; Lee, Kevin; Cort, Lucinda; O’Day, Diana R.; Dempsey, Jennifer C.; Phelps, Ian G.; Micks, Elizabeth; Benson, Lyndsey S.; Deng, Mei; Doherty, Dan; Prager, Sarah; Glass, Ian A.; et al. (PLOS ONE, 2026)
Background Agents such as digoxin and potassium chloride are frequently administered to arrest fetal circulation prior to termination procedures. Although this practice is common, the impact of delayed evacuation on human fetal tissue quality has not been systematically assessed. High-quality tissue is essential for accurate diagnosis of fetal abnormalities and for biomedical research. Objective To evaluate the effects of induced fetal demise and delayed evacuation on human fetal tissue quality across multiple organ systems, and to determine whether digoxin independently contributes to tissue degradation. Study Design Tissue was collected from second-trimester dilation and evacuation procedures performed either after induced demise with digoxin or potassium chloride followed by evacuation 19–25 hours later, or without prior induction (immediate evacuation). Brain, lung, kidney, liver, and muscle were evaluated for morphology, proliferation, apoptosis, cell viability, culture success, and nucleic acid integrity. To model in utero conditions, tissues were incubated at 37 °C or 4 °C for up to 18 hours, with and without digoxin. Results Delayed evacuation was associated with structural disruption, reduced proliferation, increased apoptosis, diminished fibroblast viability, and reduced RNA integrity compared to immediate evacuation. DNA integrity remained robust, with all samples suitable for PCR. Digoxin alone did not significantly alter RNA quality; however, when combined with prolonged incubation at 37 °C, RIN and DV200 values were significantly reduced across multiple tissues. Conclusion Warm ischemia following circulatory arrest is the principal driver of tissue degradation, with RNA and cell viability most affected and DNA relatively preserved. Digoxin alone has minimal effect but accelerates degradation under warm conditions. Minimizing the interval between circulatory arrest and evacuation, and avoiding prolonged exposure to body temperature, may preserve tissue integrity and improve the diagnostic and research utility of HFT.